2013
DOI: 10.1021/jp401665r
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of N and B Doping on Graphene and the Adsorption and Migration Behavior of Pt Atoms

Abstract: We utilize periodic density functional theory to study singly and triply Nand B-substituted graphene. We examine their doping mechanisms and effects on Pt atom adsorption and migration on graphene. We find a seemingly contradictory behavior between dopant type (n-vs p-type) and charge accumulation on the dopant atoms: the N atoms in both n-type singly N-doped graphene (NG) and p-type triply N-doped graphene (3NG) gain electron density while the B atoms in both singly (BG) and triply (3BG) Bdoped graphene are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 52 publications
9
65
0
Order By: Relevance
“…Meanwhile, Mn elements not only promote the graphitization and thus electron conductivity of CNFs, but also can enhance the catalyst tolerance to the poisoning species. Additionally, heteroatom-doped carbon itself has certain electrocatalytic activity and may exhibit synergistically enhanced performance when used as support [26][27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Mn elements not only promote the graphitization and thus electron conductivity of CNFs, but also can enhance the catalyst tolerance to the poisoning species. Additionally, heteroatom-doped carbon itself has certain electrocatalytic activity and may exhibit synergistically enhanced performance when used as support [26][27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that that these defects limit nanoparticle agglomeration, likely serving as trapping sites. 16,28 There is some debate as to the actual functional groups present in these types of systems and some recent studies have suggested these nitrogen clusters may be the start of a structures observed in carbon nitride films. 25 TEM images acquired from the post-modified catalyst sample are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time there is an unequal sharing of electrons in the sp 2 σ -bonds of the dopant atoms and the adjacent C atoms. 141 In addition, to single substitutions more complex systems have also been studied, including triple substitutions with a vacancy (also called pyridinic, see Fig. 6) 141 and multiply-doped systems.…”
Section: Photovoltaic Applications and The Electronic Structure Of Grmentioning
confidence: 99%
“…141 In addition, to single substitutions more complex systems have also been studied, including triple substitutions with a vacancy (also called pyridinic, see Fig. 6) 141 and multiply-doped systems. 140,156 The effect of nitrogen doping through the covalent bonding of N-containing aromatic species, e.g.…”
Section: Photovoltaic Applications and The Electronic Structure Of Grmentioning
confidence: 99%